Experiencing opera in the contemporary world: theoretical reflections and case studies in Nottingham and London - Moreno Zayas, Cesar Octavio (2020)
The Experience of Opera stands here as a term, as well as a methodology, to approach the studies in opera. The event of the opera is considered here in its broader sense, so, it will study the performance, but also the peripheral elements around it, which enrich the experience, and turn it, individual. Via the exploration of cities of London and Nottingham, as case studies, the work will explore the possibilities of management of the experience. The exploration involves also the study of the relationship between the audience and the opera company to uncover the power influences of them; it implies the description of a dialogue. Chapters one and two will settle the theoretical framework and first tools for the analysis. Chapter three will exanimate the cases and establish the distinctive traits of the experiences. The work continues with a revision of the theory and research tools in chapter four. Moreover, chapter five concludes with further samples of research, to enrich the probabilities of direct application of the theory of the experience of opera into the academic sphere, as well as the opera-making arena. This work develops a theoretical framework that includes the study of elements such as the opera context, expectations, homework, zone, or audience, but also uses the model of language functions, proposed by Roman Jakobson, to study the intentions of the opera companies to highlight one element more than others. So, in the end, we may conclude that everybody does opera, but not everybody does it in the same way. The study of those variations is, therefore, at the core of the current work, and its immediate application is the aim of it.